Association of Gastric Myoelectrical Activity With Ghrelin, Gastrin, and Irisin in Adults With Metabolically Healthy and Unhealthy Obesity - Abulmeaty, Mahmoud M. A.; Aldisi, Dara; Aljuraiban, Ghadeer S.; Almajwal, Ali; El Shorbagy, Eman; Almuhtadi, Yara; Albaran, Batool; Aldossari, Zaid; Alsager, Thamer; Razak, Suhail; Berika, Mohammed; Al Zaben, Mohamed (Frontiers in Physiology, 2022)
Background and Objective: Functional disturbances of gastric myoelectric activity (GMA) might exist in obesity, however, its association with the gastric hormones in obesity phenotypes is lacking. The association of the GMA with the serum levels of key gastric hormones in different obesity phenotypes was studied here. Methods: A total of 139 adults (31.00±11.12 years) were classified into different metabolic phenotypes of obesity: a) Normal weight-lean (NWL group): BMI <25 kg/m2, and the fat-mass index (FMI) ≤9.7 kg/m2 in females, and ≤6.3 kg/m2 in males; b) Metabolically obese normal weight (MONW group): BMI <25 kg/m2, FMI >9.7 kg/m2 in females, and >6.3 kg/m2 in males, c) Metabolically healthy obese (MHO group): BMI ≥25, FMI ≤9.7 kg/m2 in females, and ≤6.3 kg/m2 in males; and d) Metabolically unhealthy obese MUO group: BMI ≥25, FMI >9.7 kg/m2 in females, and >6.3 kg/m2 in males. The GMA was measured at baseline and post-prandial state using a multichannel electrogastrography with a water load satiety test. The average power distribution by frequency region and the average dominant frequency were used for analysis. Anthropometric measurements and bioelectric impedance analysis were done to calculate FMI and fat-free mass index (FFMI). Serum levels of ghrelin, gastrin, and irisin were measured by ELISA kits according to manufacturer protocol. Results: Compared to the NWL group, gastrin and ghrelin levels were significantly lower in the MUO participants while irisin was significantly higher. The EGG showed significantly lower baseline and 20-min normogastria frequencies in the MHO and MUO groups. In the MHO group, baseline duodenal frequency was positively correlated with the gastrin level while normogastria times were positively associated with irisin level and negatively with ghrelin level. In the MUO group, percentages of bradygastria frequencies at 10, 20, and 30 mins were correlated positively with the BMI and FFMI. This bradygastria was correlated positively with irisin level and negatively ghrelin level. Conclusion: The EGG patterns might be associated with obesity-related gastric hormones in different obesity phenotypes. EGG may be a promising clinical tool in obesity assessment. The association of the EGG patterns with hormonal levels needs further investigation for potential practical uses.